Com Medeia solitária no banco dos réus - Leão, Delfim (2018)
This study addresses the legal status of Medea in the light of the Attic law, taking as reference her characterization in the homonymous tragedy of Euripides. Her legal situation, her conflict with Creon and Jason and the way she involves her children in a reprisal with strong personal motivations are analysed in parallel with the version of the same theme by Seneca. Finally, is made a brief evocation of the personal seclusion of the young Esmeralda, at the end of Victor Hugo’s Notre-Dame de Paris, in which may be detected a possible influence of the characterization of Medea.